The Influence Of Interactive Learning Media In Improving Students' Critical Thinking Skills In Computer System Subjects Software Utilisation - Putri, Iin Arfani; Suharti, Suharti; Ramdhani, Lisda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Interactive learning media refers to education that utilises multimedia or information and communication technology. the problem faced by researchers in the field, the results of researcher observations, found the problem of low critical thinking skills of computer system students in software utilisation subjects. This research was conducted in an effort to determine how interactive media can improve critical thinking skills. This study uses a quantitative approach with the type of experimental research, the samples in this study were student representatives in the Experiment class with a total of 14 students and a control class of 14 people. The research instruments used tests, observation sheets, and questionnaires. The conclusion of this study is that the t-test in the experimental class with a p-value <0.05 shows that interactive media can be a useful teaching tool to improve students' critical thinking skills. Compared to traditional teaching techniques, the inclusion of interactive media in the curriculum can be more beneficial in helping students develop their critical thinking skills.Interactive learning media refers to education that utilises multimedia or information and communication technology. the problem faced by researchers in the field, the results of researcher observations, found the problem of low critical thinking skills of computer system students in software utilisation subjects. This research was conducted in an effort to determine how interactive media can improve critical thinking skills. This study uses a quantitative approach with the type of experimental research, the samples in this study were student representatives in the Experiment class with a total of 14 students and a control class of 14 people. The research instruments used tests, observation sheets, and questionnaires. The conclusion of this study is that the t-test in the experimental class with a p-value <0.05 shows that interactive media can be a useful teaching tool to improve students' critical thinking skills. Compared to traditional teaching techniques, the inclusion of interactive media in the curriculum can be more beneficial in helping students develop their critical thinking skills.